La Préhistoire du Jura et l'Europe néolithique en 100 mots-clés 5300-2100 av J.-C. - Pétrequin, Pierre (Les Cahiers de la MSHE Ledoux, 2021)
Trained in ethnoarchaeology in New Guinea, the authors offer an original reading of the historical trajectory of the first farming communities between 5300 and 2400 BC, where the micro-regions - here the Jura and the Saône plains - were deeply integrated into complex networks for the circulation of sign objects and ideas. On the scale of Western Europe, these long-distance transfers were supported by social competition, the display of inequalities, and religious imagination. 100 keywords from the archaeological vocabulary allow us to explore different social interpretations hidden behind the objects and behaviours of Neolithic populations.